Residue hydrodemetallization catalyst and method for making same
Patent Information
- Application Number
- CN202510570067.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
但是,由于渣油中金属等杂原子的存在,使得渣油加氢催化剂在反应过程中易因金属和积碳的沉积而失活,而脱金属催化剂在固定床渣油加氢催化剂级配体系中的位置相对靠前,承担了较多的反应负荷,因此,开发一种寿命更长、加氢性能更好的加氢处理催化剂、尤其是加氢脱金属催化剂就显得尤为重要
[0080]本发明提供了一种渣油加氢脱金属催化剂的制备方法,首先制备含第一活性金属的氧化铝载体,然后进行覆碳处理得到表面覆碳膜的载体,最后再用含第二活性金属的“内水相/油相/外水相”型浸渍液浸渍上述载体,得到所述催化剂。本发明方法通过各步骤的综合协调,最终制得的重、渣油加氢脱金属催化剂,抗积碳性能、脱金属活性与容金属能力均大幅提高,能够保证装置的长周期稳定运行。
Smart Images

Figure BDA0005386939350000141 
Figure BDA0005386939350000151 
Figure BDA0005386939350000152
Abstract
Description
Technical Field
[0001] This invention relates to a hydrodemetallization catalyst, specifically to a hydrodemetallization catalyst and its preparation method in the process of hydrotreating residual oil. Background Technology
[0002] With the increasing severity and deterioration of crude oil quality, coupled with the growing market demand for light oil products, heavy oil hydrotreating technology has gradually become a focus of attention in the petrochemical industry. Fixed-bed residue hydrotreating technology is mature and widely applied, serving as a crucial means to achieve clean and efficient utilization of vacuum residue. However, the presence of metals and other heteroatoms in the residue makes hydrotreating catalysts prone to deactivation during the reaction process due to metal and carbon deposition. Since demetallization catalysts occupy a relatively prominent position in the fixed-bed residue hydrotreating catalyst gradation system and bear a significant reaction load, developing a hydrotreating catalyst with a longer lifespan and better hydrotreating performance, especially a hydrodemetallization catalyst, is of paramount importance.
[0003] Currently, research on hydrogenation demetallization catalysts mainly focuses on the pore size of the support, such as introducing pore-expanding agents and acid treatment during the support preparation process. However, the acidity distribution on the surface of the support prepared by these methods is uneven, and the introduction of additives destroys the original pores of the support, which is not conducive to the dispersion of active metals in the subsequent impregnation process. As a result, the catalyst has poor hydrogenation performance, poor resistance to metal deposition, and poor resistance to carbon buildup.
[0004] CN104549331A discloses a method for preparing a hydrodemetallization catalyst, comprising the following steps: (1) preparing a mixture of alumina dry gel powder and water; (2) treating the material obtained in step (1) with dual-frequency microwaves at a temperature of 100–300°C, preferably 150–250°C, for a time of 1–6 h, preferably 2–4 h, with a frequency difference of 1–50 kHz, preferably 5–35 kHz, and filtering and drying after treatment; (3) mixing the material obtained in step (2) with a salt solution containing an active metal, and then drying and calcining to obtain the hydrodemetallization catalyst. The hydrodemetallization activity and stability of the hydrodemetallization catalyst prepared by this method need to be further improved. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a catalyst for the hydrodemetallization of heavy and residual oils and its preparation method. When used in the hydrodemetallization reaction of heavy and residual oils, this catalyst exhibits strong hydrogenation activity, significantly improved anti-carbon deposition performance, demetallization activity, and metal-containing capacity, ensuring long-term stable operation of the equipment.
[0006] The first aspect of this invention provides a method for preparing a hydrodemetallization catalyst for residue oil, comprising the following steps:
[0007] (1) Preparation of alumina support containing the first active metal;
[0008] (2) The carrier obtained in step (1) is subjected to surface carbon coating treatment and calcined to obtain carrier A with surface carbon coating film.
[0009] (3) Impregnate the carrier A obtained in step (2) with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, dry and calcine to obtain the catalyst.
[0010] Further, in step (1), the method for preparing the alumina support containing the first active metal includes:
[0011] (I) Mix boehmite, first active metal, alkaline additive, and water (preferably deionized water), grind, and filter to obtain solid material;
[0012] (II) The solid material obtained in step (I) is mixed with an adhesive, molded, dried, and calcined to obtain an alumina carrier containing the first active metal.
[0013] Further, in step (I), the mass content of alumina in the pseudoboehmite is 60.0% to 75.0%. The pseudoboehmite is prepared using conventional methods, such as the aluminum sulfate method, the aluminum alkoxide method, and the sol-gel method.
[0014] Further, in step (I), the alkaline auxiliary agent is one or more alkaline compounds such as sodium hydroxide, potassium hydroxide, and sodium carboxylate (e.g., sodium acetate, sodium formate).
[0015] Further, in step (I), the first active metal is at least one of Group VIII metals; the Group VIII metal is preferably Ni and / or Co, more preferably Ni, the Ni source is selected from at least one of basic nickel carbonate, nickel sulfate, nickel nitrate, etc., and the Co source is selected from at least one of cobalt nitrate, cobalt sulfate, etc.
[0016] Further, in step (I), the mass ratio of pseudoboehmite (calculated as alumina), first active metal (calculated as oxide), alkaline additive, and water is 200–240: 1.0–10.0: 6.0–15.0: 120–180.
[0017] Furthermore, in step (I), the grinding can be performed using methods such as ball milling or sand milling. The ground material not only exhibits more uniform metal dispersion, but the alkaline additive also forms a "first protective film" on the surface of the dried material. The filtration process is a standard procedure in the art. The resulting ground sample has an average particle size of 2.0–10.0 μm.
[0018] Furthermore, in step (I), the first active metal is a co-active metal, which can interact with the support during the calcination process to weaken the acidity of the support, and can also work synergistically with the main active metal (such as Mo) in the second active metal, which is beneficial to the hydrogenation reaction.
[0019] Further, in step (II), the adhesive may be an organic acid and / or an inorganic acid, wherein the inorganic acid may be one or more of nitric acid, sulfuric acid, boric acid, and phosphoric acid, and the organic acid may be one or more of tartaric acid, citric acid, and oxalic acid.
[0020] Further, in step (II), the mass of the adhesive is 0.5% to 5.0% of the mass of boehmite in step (1) based on alumina.
[0021] Furthermore, in step (II), the forming method can be at least one of extrusion, sheeting, and ball rolling. The formed shape can be clover-shaped, four-leaf clover-shaped, butterfly-shaped, cylindrical, spherical, or strip-shaped, etc.
[0022] Further, in step (II), molding aids, such as at least one of extrusion aids and deionized water, can be added during the molding process according to molding requirements. The extrusion aid can be one or more of methylcellulose, ethylcellulose, guar gum, and starch. The mass of the extrusion aid added is 0.5% to 8.0% of the mass of boehmite (based on alumina). The amount of deionized water used can be 80% to 120% of the mass of boehmite (based on alumina) in step (I).
[0023] Furthermore, in step (II), the drying temperature is 120–200°C and the drying time is 2–12 hours.
[0024] Further, in step (II), the roasting adopts a two-stage roasting process. The first stage roasting temperature is 350–450℃, the roasting time is 2–6 hours, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably air. The second stage roasting temperature is 450–750℃, the roasting time is 2–8 hours, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably nitrogen. The second stage roasting temperature is 150–300℃ higher than the first stage roasting temperature.
[0025] Further, in step (2), the carbon coating treatment uses an aqueous emulsion containing a polymer compound and water-soluble cellulose. The polymer compound is not particularly limited and can be selected from one or more of polyimide, polyfurfuryl alcohol, and phenolic resin. The water-soluble cellulose is one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose. In the aqueous emulsion, the mass content of the polymer compound is 5.0%–15.0%, and the mass content of the water-soluble cellulose is 0.5%–3.0%.
[0026] Further, in step (2), the amount of the aqueous emulsion (in mL) and the carrier obtained in step (1) is 0.8 to 1.5 mL / g.
[0027] Further, in step (2), after the surface carbon coating treatment is completed, the substrate is first filtered, washed, and dried using conventional methods, and then calcined to obtain a carrier A with a carbon-coated film. The drying temperature is 120–200℃, and the drying time is 2.0–12.0 h. The calcination conditions are: temperature 500–700℃, time 2.0–8.0 h, and the calcination atmosphere is an inert atmosphere, preferably one or more of nitrogen and argon.
[0028] Further, in step (3), the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal includes an inner aqueous phase, an oil phase covering the inner aqueous phase, and an outer aqueous phase. The inner aqueous phase includes a Group VIB metal source, a co-emulsifier, a water-soluble polymer, water, and an optional auxiliary agent source. The outer aqueous phase includes a Group VIII metal source, a hydrophilic agent, and water. The oil phase includes a surfactant and oil.
[0029] Further, the mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0, more preferably 1.0:4.0 to 10.0, for example 1.0:4.0, 1.0:4.5, 1.0:5.0, 1.0:5.5, 1.0:6.0, 1.0:6.5, 1.0:7.0, 1.0:7.5, 1.0:8.0, 1.0:8.5, 1.0:9.0, 1.0:9.5, 1.0:10.0, etc., and any value within the range formed by any two of these values.
[0030] Furthermore, the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, 9.0:1.0, etc., and any value within the range formed by any two of these values.
[0031] Furthermore, the mass ratio of the "internal aqueous phase / oil phase" to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0, for example 0.5:1.0, 0.7:1.0, 0.9:1.0, 1.0:1.0, 1.5:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0, etc., and any value within any range formed by any two of these values. The mass of the "internal aqueous phase / oil phase" refers to the total mass of the internal aqueous phase and the oil phase coating the internal aqueous phase.
[0032] Furthermore, the water-soluble polymer is one or more of polyvinyl alcohol (molecular weight 170,000 to 220,000), carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate (molecular weight less than 10,000).
[0033] Furthermore, in the internal aqueous phase, the mass concentration of the water-soluble polymer is 4.0% to 14.0%.
[0034] Furthermore, in the inner aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; in the outer aqueous phase, the concentration of Group VIII metals as oxides is 2-50 g / 100 mL, preferably 5-30 g / 100 mL.
[0035] Further, the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co. The Group VIB metal source is one or more of ammonium molybdate, ammonium metatungstate, and molybdenum oxide, and the Group VIII metal source is one or more of basic nickel nitrate, nickel sulfate, nickel nitrate, and cobalt nitrate.
[0036] Furthermore, in the internal aqueous phase, the auxiliary agent is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source is one or more of phosphoric acid, ammonium hydrogen phosphate, and ammonium dihydrogen phosphate. In the internal aqueous phase, the concentration of the auxiliary agent, calculated as an oxide, is 0–12.0 g / 100 mL, preferably 0.5–12.0 g / 100 mL.
[0037] Further, the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, and glycerin. The mass concentration of the co-emulsifier in the internal aqueous phase is 0.5% to 5.0%.
[0038] Further, the hydrophilic agent is one or more selected from polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide. The mass concentration of the hydrophilic agent in the external aqueous phase is 4.0% to 15.0%.
[0039] Furthermore, the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc.
[0040] Furthermore, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0041] Further, in step (3), the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal includes:
[0042] (a) The surfactant and oil are mixed and heated to obtain the oil phase;
[0043] (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution;
[0044] (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase;
[0045] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion.
[0046] (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase;
[0047] (f) The “inner aqueous phase / oil phase” type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0048] Further, in step (a), the surfactant is selected from glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol (structure R-(OCC)). x -OH, where R is a straight-chain alkyl group with 12 to 15 carbon atoms, and x is 2 to 11, etc., or one or more of these. The oil may be at least one of silicone oil and vegetable oil, wherein the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
[0049] Furthermore, in step (a), the heating is carried out to a temperature of 45–85°C to make the oil phase appear as a uniform liquid.
[0050] Further, in step (a), the mass ratio of the added surfactant to the mass of oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0.
[0051] Further, in step (b), the co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, polyvinyl alcohol, and glycerin.
[0052] Further, in step (b), the amount of the co-emulsifier is 0.5% to 5.0% of the mass of the internal aqueous phase obtained in step (c).
[0053] Further, in step (b), the Group VIB metal is preferably Mo and / or W; the Group VIB metal source can be one or more of molybdenum oxide, ammonium tetramolybdate, ammonium heptamolybdate, ammonium metatungstate, etc. The auxiliary agent is selected from at least one of phosphorus, silicon, or boron, preferably phosphorus, and the phosphorus source can be one or more of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, etc.
[0054] Further, in step (b), the water is distilled water or deionized water, and the conductivity of the water is less than 10.0 mS.
[0055] Further, in step (b), the heating is carried out to a temperature of 90-120°C to ensure that the substances added in step (b) are mixed evenly until a clear solution is obtained.
[0056] Further, in step (c), the concentration of Group VIB metals as oxides in the internal aqueous phase is 8-80 g / 100 mL, preferably 10-60 g / 100 mL, and the concentration of additives as oxides is 0-12.0 g / 100 mL, preferably 0.5-12.0 g / 100 mL.
[0057] Further, in step (c), the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate.
[0058] Further, in step (c), the mass concentration of the water-soluble polymer in the aqueous phase obtained in step (c) is 4.0% to 14.0%.
[0059] Furthermore, in step (d), the oil phase is kept in a liquid state at a temperature of 45–85°C, and the stirring rate is 400–800 r / min.
[0060] Further, in step (d), the mass ratio of the internal aqueous phase to the oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0.
[0061] Further, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a homogenization time of 3 to 8 minutes, and a homogenization temperature of 50 to 85°C.
[0062] Further, in step (e), the Group VIII metal is Ni and / or Co. The Group VIII metal source is one or more of basic nickel carbonate, nickel sulfate, nickel nitrate, cobalt nitrate, etc.
[0063] Further, in step (e), the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide.
[0064] Further, in step (e), the water is distilled water or deionized water, and the conductivity of the water should be less than 10.0 mS.
[0065] Further, in step (e), the mass concentration of the hydrophilic agent in the external aqueous phase is 5.0% to 15.0%.
[0066] Further, in step (e), the concentration of Group VIII metals in the external aqueous phase, calculated as oxides, is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL.
[0067] Further, in step (e), the mass ratio of the "internal aqueous phase / oil phase" emulsion to the external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.0.
[0068] Furthermore, in the catalyst, the mass of Group VIII metals introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, based on oxides, accounts for 50.0% to 85.0% of the total Group VIII metal loading based on oxides in the catalyst.
[0069] Furthermore, in step (3), the impregnation method is saturated impregnation.
[0070] Furthermore, in step (3), the drying temperature is 120-200℃ and the drying time is 2-12h.
[0071] Further, in step (3), the calcination conditions are: calcination temperature of 550-750℃, calcination time of 2-10h, and calcination atmosphere of a mixture of air and water vapor, wherein the volume ratio of air to water vapor is 0.1-5.0:1.0.
[0072] The second aspect of the present invention provides a residue oil hydrodemetallization catalyst prepared by the preparation method described in the first aspect.
[0073] Further, the catalyst comprises an alumina support containing a first active metal and a second active metal, wherein the first active metal is at least one of a Group VIII metal, and the second active metal comprises at least one of a Group VIB metal and at least one of a Group VIII metal. Further, the Group VIII metal is preferably Ni and / or Co, and the Group VIB metal is preferably Mo and / or W.
[0074] Furthermore, the first active metal is dispersed in the alumina support phase; the mass ratio of the first active metal, as an oxide, to the alumina is 0.01 to 0.10:1, for example, but not limited to, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.07:1, 0.08:1, 0.09:1, 0.10:1, etc., and any value within the range formed by any two of these values.
[0075] Furthermore, in the catalyst, based on the mass of the catalyst, the content of Group VIB metal oxides is 10.0% to 20.0%, and the content of Group VIII metal oxides is 2.0% to 10.0%. The mass ratio of the Group VIII metal in the first active metal (calculated as oxide) to the Group VIII metal in the second active metal (calculated as oxide) is 0.1 to 3.0:1.
[0076] Furthermore, the specific surface area of the catalyst is 165–185 m². 2 / g, with a pore volume of 0.60–0.85 mL / g; preferably, the catalyst has a specific surface area of 170–180 m² / g. 2 / g, with a pore volume of 0.65~0.75mL / g.
[0077] Furthermore, the catalyst also includes an auxiliary agent selected from at least one of phosphorus, silicon, or boron, preferably phosphorus. Furthermore, the auxiliary agent, based on the mass of the catalyst, comprises 1.0% to 5.0% in terms of oxides.
[0078] The third aspect of this invention provides the application of the above-mentioned catalyst in the hydrotreating of heavy oil and residual oil.
[0079] Compared with the prior art, the present invention has the following beneficial effects:
[0080] This invention provides a method for preparing a hydrodemetallization catalyst for heavy and residual oils. First, an alumina support containing a first active metal is prepared. Then, a carbon coating treatment is performed to obtain a support with a carbon-coated surface. Finally, the support is impregnated with an "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal to obtain the catalyst. Through the comprehensive coordination of each step, the method of this invention ultimately yields a hydrodemetallization catalyst for heavy and residual oils that significantly improves its resistance to carbon deposition, demetallization activity, and metal-containing capacity, ensuring long-term stable operation of the equipment.
[0081] This invention employs the introduction of a portion of active metal (i.e., a first active metal) during the support preparation process. This introduced active metal is first dispersed within the alumina support bulk phase. During the reaction, this reduces the reaction intensity on the catalyst surface, increasing the ability of macromolecules to further penetrate the catalyst interior. During support preparation, the first active metal (co-active metal) is added during grinding, resulting in more uniform metal dispersion. Simultaneously, the introduced alkaline additive weakens the interaction between the first active metal (e.g., nickel) and alumina during support formation. Then, the support is coated with a carbon film. The carbon film ensures that the subsequent second active metal does not contact the already loaded and dispersed first active metal during impregnation, while the second active metal is uniformly dispersed on the carbon film. Finally, after calcination in a mixed atmosphere, air is introduced to remove the carbon film, leaving the second active metal uniformly dispersed on the support. Furthermore, carbon coating is performed on the alumina support containing the first active metal, followed by inert gas calcination. As moisture gradually evaporates, the latex particles are gradually extruded to form a thin film containing crosslinkable groups, which crosslink to form a three-dimensional network film. This film temporarily provides a loading site for the second active metal. After the catalyst is calcined, the film disappears. Finally, the second active metal is impregnated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution, which uniformly disperses it on the alumina support containing the first active metal and works in conjunction with the first active metal, which is beneficial to improving the activity and stability of hydrodemetallization. Furthermore, this invention employs an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing a second active metal to impregnate and load the second active metal. Utilizing the properties of the high dispersion of the inner aqueous phase in the oil phase and the high dispersion of the "inner aqueous phase / oil phase" in the outer aqueous phase, the inner aqueous phase serves as the carrier matrix for Group VIB metals, while the outer aqueous phase serves as the carrier matrix for Group VIII metals. The oil phase then loads and isolates the metals in the inner and outer aqueous phases, which optimizes the distribution of the active metal in the catalyst during impregnation and prevents aggregation during the disappearance of the carbon film.
[0082] In the preparation process of the "inner aqueous phase / oil phase / outer aqueous phase" impregnation solution containing a second active metal, the present invention firstly disperses the Group VIB metal in the form of ions in the inner aqueous phase using a co-emulsifier, thus obtaining an inner aqueous phase containing the Group VIB metal. To control the particle size and maintain the particle size distribution during the subsequent formation of the "inner aqueous phase / oil phase" emulsion, a water-soluble polymer is added to the obtained inner aqueous phase as a "protective layer" for the particles. This water-soluble polymer adsorbs onto the surface of the particles during the subsequent formation of the "inner aqueous phase / oil phase" emulsion, forming a "surface layer" of a certain thickness, which effectively hinders collisions and aggregation between particles, further improving the stability of the system. Next, the Group VIII metal is dispersed in the form of ions in water containing a hydrophilic agent, thus obtaining the outer aqueous phase. Then, under specific conditions, the above-mentioned "inner aqueous phase / oil phase" emulsion is further dispersed in the outer aqueous phase, finally obtaining the hydrogenation catalyst impregnation solution.
[0083] The catalyst of this invention is used in the hydrodemetallization reaction of heavy and residual oils. It has strong hydrogenation activity, and its anti-carbon deposition performance, demetallization activity and metal-containing capacity are all greatly improved, which can ensure the long-term stable operation of the unit. Detailed Implementation
[0084] The technical solutions and effects of the present invention will be further illustrated below with reference to the embodiments, but the invention is not limited to the following embodiments.
[0085] In this invention, the pore structure and specific surface area of the catalyst are characterized using the Mack ASAP-2420 physical adsorption instrument.
[0086] Unless otherwise specified, all experimental materials used in this invention were purchased from conventional biochemical reagent manufacturers.
[0087] Example 1
[0088] The preparation method of the alumina support containing the first active metal includes:
[0089] (I) Mix 300g of boehmite (alumina content 74.0%), 9.8g of basic nickel carbonate (nickel oxide content 52.0%), 8.5g of alkaline additive NaOH, and 140g of deionized water, grind (average particle size of the sample after grinding is 5.0μm), filter, and obtain solid material.
[0090] (II) The solid material obtained in step (I) is mixed with 9.4g of nitric acid, 7.5g of guar gum powder, and 200g of deionized water, and then extruded into a four-leaf clover shape. After drying and calcining (drying temperature is 120℃, drying time is 6h. The calcination process adopts two stages: the first stage calcination temperature is 450℃, calcination time is 3h, and the calcination atmosphere is air; the second stage calcination temperature is 700℃, calcination time is 3h, and the calcination atmosphere is nitrogen), an alumina carrier containing the first active metal (Ni) is obtained.
[0091] The preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal includes:
[0092] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:6.0. The co-emulsifier is polyethylene glycol-400, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is aluminum monostearate. The mass ratio of co-emulsifier: molybdenum source (calculated as molybdenum oxide): phosphorus source (calculated as phosphorus oxide): water-soluble polymer: water is 20:265:59.7:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.8. The mass ratio of nickel source (calculated as oxide): hydrophilic agent: water is 11.2:32:400. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 0.8:1.0.
[0093] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0094] (b) Add the co-emulsifier polyethylene glycol-400, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, the temperature is maintained for 4 hours. The stirring speed is kept constant until a clear solution is obtained.
[0095] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0096] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0097] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0098] (f) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (d) to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0099] The preparation method of the catalyst in this example includes:
[0100] (1) Preparation of alumina support containing the first active metal;
[0101] (2) The carrier obtained in step (1) is mixed evenly with an aqueous emulsion containing polyimide and hydroxymethyl cellulose, dried at 150°C for 8 hours, and calcined at 650°C for 5 hours under a nitrogen atmosphere to obtain a carrier A with a carbon film on the surface; wherein, the mass content of polyimide in the aqueous emulsion is 8.0% and the mass content of hydroxymethyl cellulose is 0.8%; the ratio of the amount of aqueous emulsion (by volume mL) to the amount of carrier obtained in step (1) (by mass g) is 1.0 mL / g;
[0102] (3) The carrier A obtained in step (2) is impregnated with the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation liquid containing the second active metal in a saturated impregnation manner, and then dried at 150°C for 4 hours. It is then calcined at 600°C for 4 hours in a mixed atmosphere of air and water vapor (air and water vapor volume ratio of 1:2) to obtain catalyst CAT-1.
[0103] Example 2
[0104] The preparation method of the alumina support containing the first active metal includes:
[0105] (I) 277g of boehmite (alumina content 74.0%), 4.2g of basic nickel carbonate (nickel oxide content 52.0%), 6.5g of alkaline additive NaOH, and 125g of deionized water were mixed, ground (the average particle size of the sample after grinding was 5.0μm), and filtered to obtain solid material.
[0106] (II) The solid material obtained in step (I) is mixed with 9.4g of nitric acid, 6.0g of guar gum powder, and 200g of deionized water, and then extruded into a four-leaf clover shape. After drying and calcining (drying temperature is 120℃, drying time is 6h. The calcination process adopts two stages: the first stage calcination temperature is 400℃, calcination time is 3h, and the calcination atmosphere is air; the second stage calcination temperature is 650℃, calcination time is 3h, and the calcination atmosphere is nitrogen), an alumina carrier containing the first active metal (Ni) is obtained.
[0107] Methods for preparing "internal aqueous phase / oil phase / external aqueous phase" type impregnation solutions containing a second active metal include:
[0108] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:8.0. The co-emulsifier is polyethylene glycol-8000, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 20:265:59.4:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.5. The mass ratio of nickel source (oxidant):hydrophilic agent:water is 14.4:32:400. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 1.0:1.0.
[0109] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 80°C, and wait for the silicone oil to melt to obtain the oil phase;
[0110] (b) Add the co-emulsifier polyethylene glycol-8000, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, the temperature is maintained for 4 hours. The stirring speed is kept constant until a clear solution is obtained.
[0111] (c) Add water-soluble polymer polyvinyl alcohol to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0112] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 80°C, and the mixture is stirred. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0113] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0114] (f) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (d) to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0115] The catalyst in this example was prepared according to the method in Example 1, resulting in catalyst CAT-2.
[0116] Example 3
[0117] The preparation method of the alumina support containing the first active metal includes:
[0118] (I) Mix 300g of boehmite (alumina content 74.0%), 18.3g of basic nickel carbonate (nickel oxide content 52.0%), 8.5g of alkaline additive NaOH, and 140g of deionized water, grind (average particle size of the sample after grinding is 5.0μm), filter, and obtain solid material.
[0119] (II) The solid material obtained in step (I) is mixed with 9.4g of nitric acid, 7.5g of guar gum powder, and 200g of deionized water, and then extruded into a four-leaf clover shape. After drying and calcining (drying temperature is 120℃, drying time is 6h. The calcination process adopts two stages: the first stage calcination temperature is 450℃, calcination time is 3h, and the calcination atmosphere is air; the second stage calcination temperature is 700℃, calcination time is 3h, and the calcination atmosphere is nitrogen), an alumina carrier containing the first active metal (Ni) is obtained.
[0120] The preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal includes:
[0121] In this example, the surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:9.0. The co-emulsifier is cetyl alcohol, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is carboxymethyl cellulose, and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 9:265:60.7:121:400. The mass ratio of oil phase to internal aqueous phase is 1.0:7.0. The mass ratio of nickel source (calculated as oxide):hydrophilic agent:water is 79:22.2:400. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 6.0:1.0.
[0122] (a) Add the surfactant glyceryl monostearate to the silicone oil, heat to 75°C, and wait for the silicone oil to melt to obtain the oil phase;
[0123] (b) Add the co-emulsifier cetyl alcohol, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 400 r / min. When the temperature is raised to 110°C, the temperature is maintained for 3 hours. The stirring speed is kept constant until a clear solution is obtained.
[0124] (c) Add water-soluble polymer carboxymethyl cellulose to the clear solution obtained in step (b) to obtain an inner aqueous phase;
[0125] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the addition, the temperature of the oil phase is maintained at 75°C, and the mixture is stirred. The shear homogenization rate is 14000 rpm, the shear homogenization time is 4 min, and the temperature during the shear homogenization process is 70°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0126] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0127] (f) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (d) to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0128] The catalyst in this example was prepared according to the method in Example 1, resulting in catalyst CAT-3.
[0129] Example 4
[0130] The alumina carrier containing the first active metal in this example is the same as in Example 1.
[0131] The preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal includes:
[0132] In this example, the surfactant is glyceryl distearate, the silicone oil is phenyl silicone oil, and the mass ratio of surfactant to silicone oil is 1.0:6.0. The co-emulsifier is propylene glycol, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is sodium polyacrylate, and the hydrophilic agent is polysorbate. The mass ratio of co-emulsifier:molybdenum source (calculated as molybdenum oxide):phosphorus source (calculated as phosphorus oxide):water-soluble polymer:water is 39:265:60.3:32:400. The mass ratio of oil phase to internal aqueous phase is 1.0:5.0. The mass ratio of nickel source (calculated as oxide):hydrophilic agent:water is 199:62:400. The mass ratio of "internal aqueous phase / oil phase" emulsion to external aqueous phase is 5.0:1.0.
[0133] (a) Add the surfactant glyceryl distearate to the silicone oil, heat to 75°C, and wait for the silicone oil to melt to obtain the oil phase;
[0134] (b) Add the co-emulsifier propylene glycol, molybdenum oxide and phosphoric acid to deionized water in sequence. A reflux condenser is used during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 400 r / min. When the temperature is raised to 115°C, the temperature is maintained for 4 h. The stirring speed is kept constant until a clear solution is obtained.
[0135] (c) Add water-soluble sodium polyacrylate to the clear solution obtained in step (b) to obtain an internal aqueous phase;
[0136] (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a). During the dropwise addition, the temperature of the oil phase is maintained at 75°C, and the mixture is stirred. The shear homogenization rate is 16000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 70°C. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0137] (e) Add the hydrophilic agent to the water, and then add nickel nitrate to the water containing the hydrophilic agent to obtain the external aqueous phase;
[0138] (f) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (d) to the outer aqueous phase obtained in step (e) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0139] The preparation method of the catalyst in this example includes:
[0140] (1) Preparation of alumina support containing the first active metal;
[0141] (2) The carrier obtained in step (1) is mixed evenly with an aqueous emulsion containing polyfurfuryl alcohol and hydroxyethyl methylcellulose, dried at 180°C for 5 hours, and calcined at 600°C for 6 hours under a nitrogen atmosphere to obtain a carrier A with a carbon film on the surface; wherein, the mass content of polyfurfuryl alcohol in the aqueous emulsion is 10.0%, and the mass content of hydroxyethyl methylcellulose is 1.2%; the ratio of the amount of aqueous emulsion (by volume mL) to the amount of carrier obtained in step (1) (by mass g) is 1.0 mL / g;
[0142] (3) The carrier A obtained in step (2) is impregnated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal in a saturated impregnation manner, and then dried at 160°C for 3 hours. It is then calcined at 700°C for 3 hours in a mixed atmosphere of air and water vapor (air and water vapor volume ratio of 3:1) to obtain catalyst CAT-4.
[0143] Comparative Example 1
[0144] Compared with Example 1, the difference is that no alkaline additive is introduced in the preparation of the alumina support containing the first active metal in step (1). The final product is the residue oil hydrodemetallization catalyst DCAT-1.
[0145] Comparative Example 2
[0146] Compared with Example 1, the difference is that step (2) is omitted, that is, the alumina support containing the first active metal obtained in step (1) is not subjected to surface carbonization treatment, but is directly impregnated with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution loaded with the second active metal. Finally, the residue oil hydrodemetallization catalyst DCAT-2 is obtained.
[0147] Comparative Example 3
[0148] Compared with Example 1, the difference is that the solution used in the carbon coating process in step (2) is changed to a glucose aqueous solution with a mass percentage of 8.8%, and the ratio of glucose aqueous solution (by volume mL) to alumina support containing the first active metal (by mass g) is 1.0 mL / g. The final product is the residue oil hydrodemetallization catalyst DCAT-3.
[0149] Comparative Example 4
[0150] Compared with Example 1, the difference lies in that the first active metal Ni is not added in the alumina preparation in step (1), and in step (3), the amount of MoO3 introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal is 100% of the total MoO3 loading in the catalyst, and the amount of NiO introduced into the catalyst by the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal is 100% of the total NiO loading in the catalyst. Finally, the residue oil hydrodemetallization catalyst DCAT-4 is obtained.
[0151] Comparative Example 5
[0152] Compared with Example 1, the difference is that water-soluble polymers are not introduced during the preparation of the "inner aqueous phase / oil phase / outer aqueous phase" impregnation solution containing the second active metal in step (3). The final product is the residue oil hydrodemetallization catalyst DCAT-5.
[0153] Comparative Example 6
[0154] Compared with Example 1, the difference lies in the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing a second active metal, which includes:
[0155] The surfactant is glyceryl monostearate, the silicone oil is methyl silicone oil, and the surfactant to silicone oil mass ratio is 1.0:6.0. The co-emulsifier is polyethylene glycol-400, the molybdenum source is molybdenum oxide, the phosphorus source is phosphoric acid, the nickel source is basic nickel carbonate, the water-soluble polymer is polyvinyl alcohol (molecular weight 200,000), and the hydrophilic agent is aluminum monostearate. The mass ratio of co-emulsifier: molybdenum source (calculated as molybdenum oxide): phosphorus source (calculated as phosphorus oxide): water-soluble polymer: water is 20:265:59.7:70.3:400. The mass ratio of oil phase to internal aqueous phase is 1.0:0.8. The mass ratio of nickel source (calculated as oxide): hydrophilic agent: water is 11.2:32:400. The mass ratio of "internal aqueous phase / oil phase" type emulsion to external aqueous phase is 0.8:1.0.
[0156] (a) Add the co-emulsifier, molybdenum oxide, phosphoric acid, and water-soluble polymer to deionized water in the following order. Use a reflux condenser during the reaction. The reaction starts at 28°C. During the reaction, the stirring speed is 500 r / min. When the temperature is raised to 120°C, maintain this temperature for 4 hours. Maintain a constant stirring speed until a transparent and clear solution is obtained, thus obtaining the inner aqueous phase.
[0157] (b) Add basic nickel carbonate and a hydrophilic agent to water to obtain an external aqueous phase;
[0158] (c) The surfactant and silicone oil are added to the aqueous phase obtained in step (a) while stirring. The shear homogenization rate is 15000 rpm, the shear homogenization time is 5 min, and the temperature during the shear homogenization process is 60℃. After the droplets are dispersed into an emulsion, an "aqueous phase / oil phase" type emulsion is obtained.
[0159] (d) Add the “inner aqueous phase / oil phase” type emulsion obtained in step (c) to the outer aqueous phase obtained in step (b) to obtain an “inner aqueous phase / oil phase / outer aqueous phase” type impregnation solution.
[0160] The final product was DCAT-6, a catalyst for the hydrodemetallization of residue oil.
[0161] Comparative Example 7
[0162] Compared with Example 1, the difference is that the roasting process in step (3) does not use a mixed atmosphere roasting, the roasting temperature is 600℃, the roasting time is 4h, and the roasting atmosphere is air. Finally, the residue oil hydrodemetallization catalyst DCAT-7 was obtained.
[0163] Table 1. Physicochemical properties and catalyst composition of each example of hydrodemetallization catalyst.
[0164] Serial Number Example 1 Example 2 Example 3 Example 4 Catalyst number CAT-1 CAT-2 CAT-3 CAT-4 <![CDATA[specific surface area, m 2 / g]]> 176 178 173 175 <![CDATA[pore volume, cm 3 / g]]> 0.69 0.71 0.68 0.66 First active metal NiO, wt% 1.75 0.81 3.22 1.73 <![CDATA[Al2O3,wt%]]> 80.64 80.59 80.63 80.68 Second active metal <![CDATA[MoO3,wt%]]> 12.20 12.22 12.18 12.17 NiO, wt% 2.66 3.64 1.18 2.64 <![CDATA[P2O5,wt%]]> 2.75 2.74 2.79 2.77
[0165] Table 2 Physicochemical properties and catalyst composition of each comparative example of hydrogenation demetallization catalyst
[0166]
[0167]
[0168] Evaluation test
[0169] Activity stability tests were conducted on Examples 1-4 and Comparative Examples 1-7 using a 200mL fixed-bed hydrogenation test apparatus. The feedstock was residue oil with a density of 985.2 kg / m³. 3(20℃), S content 2.31wt%, Ni and V contents 26.9μg / g and 59.4μg / g respectively, CCR content 12.4wt%, the demetallization rate was 100% when the experiment was run for 2000h as in Example 1, and all other values are relative demetallization rates. Specific experimental conditions are shown in Table 3, and experimental results are shown in Tables 4 and 5.
[0170] Table 3 Experimental conditions
[0171] Reaction temperature, °C 385 Reaction pressure, MPa 15.7 <![CDATA[Liquid hourly volumetric space velocity, h -1 > 1.0 Hydrogen-to-oil ratio, V / V 700
[0172] Table 4. Test results of the hydrogenation demetallization catalysts in each example.
[0173]
[0174] Table 5. Experimental results of hydrogenation demetallization catalysts in each comparative example.
[0175]
[0176] As can be seen from Tables 1-5, the hydrodemetallization catalyst prepared according to the method of the present invention has a high specific surface area and pore volume, as well as high hydrodemetallization activity and stability, and can well meet the requirements of the hydrodemetallization process of heavy and residual oils.
Claims
1. A method for preparing a residue oil hydrodemetallization catalyst, comprising the following steps: (1) Preparation of alumina support containing the first active metal; (2) The carrier obtained in step (1) is subjected to surface carbon coating treatment and calcined to obtain carrier A with surface carbon coating film. (3) Impregnate the carrier A obtained in step (2) with an "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal, dry and calcine to obtain the catalyst.
2. The preparation method according to claim 1, characterized in that, In step (2), the carbon coating treatment uses an aqueous emulsion containing a polymer compound and water-soluble cellulose, wherein the polymer compound is one or more of polyimide, polyfurfuryl alcohol, and phenolic resin, and the water-soluble cellulose is one or more of hydroxymethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose. Preferably, the water emulsion contains 5.0% to 15.0% by mass of polymeric compounds and 0.5% to 3.0% by mass of water-soluble cellulose.
3. The preparation method according to claim 1, characterized in that, In step (2), the amount of the aqueous emulsion in mL and the amount of the carrier obtained in step (1) in g are related by volume to be 0.8-1.5 mL / g.
4. The preparation method according to claim 1, characterized in that, In step (2), the calcination conditions are: temperature of 500-700℃, time of 2.0-8.0h, and calcination atmosphere of inert atmosphere, preferably one or more of nitrogen and argon.
5. The preparation method according to claim 1, characterized in that, In step (3), the "inner aqueous phase / oil phase / outer aqueous phase" type impregnation solution containing the second active metal includes an inner aqueous phase, an oil phase covering the inner aqueous phase, and an outer aqueous phase; the inner aqueous phase includes a Group VIB metal source, a co-emulsifier, a water-soluble polymer, water, and an optional auxiliary agent source; the outer aqueous phase includes a Group VIII metal source, a hydrophilic agent, and water; and the oil phase includes a surfactant and oil.
6. The preparation method according to claim 5, characterized in that, The mass ratio of surfactant to oil is 1.0:0.1 to 10.0, preferably 1.0:2.0 to 10.0; and / or, the mass ratio of internal aqueous phase to oil phase is 0.4 to 12.0:1.0, preferably 0.5 to 9.0:1.0; and / or, the mass ratio of "internal aqueous phase / oil phase" to external aqueous phase is 0.5 to 10.0:1.0, preferably 0.5 to 8.0:1.
0.
7. The preparation method according to claim 5, characterized in that, The co-emulsifier is selected from one or more of polyethylene glycol-8000, polyethylene glycol-400, cetyl alcohol, octadecanol, propylene glycol, n-butanol, and glycerin; And / or, the water-soluble polymer is one or more of polyvinyl alcohol, carboxymethyl cellulose, gelatin, gum arabic, and sodium polyacrylate; And / or, the Group VIB metal is Mo and / or W, and the Group VIII metal is Ni and / or Co; And / or, the additive is selected from at least one of phosphorus, silicon or boron, preferably phosphorus; And / or, the hydrophilic agent is one or more of polysorbate, sorbitan monolaurate, aluminum monostearate, sodium dioctyl succinate sulfonate, benzyl ammonium chloride, and hexadecanetrimethylamine bromide; And / or, the surfactant is selected from one or more of glyceryl monostearate, glyceryl distearate, glyceryl monolaurate, and polyoxyethylene ether fatty alcohol; And / or, the oil is selected from at least one of silicone oil and vegetable oil, the silicone oil is selected from at least one of methyl silicone oil, ethyl silicone oil, phenyl silicone oil, methyl hydrogen silicone oil, and methyl phenyl silicone oil, and the vegetable oil is selected from one or more of peanut oil, coconut oil, and tea seed oil.
8. The preparation method according to claim 5, characterized in that, In the internal aqueous phase, the mass concentration of water-soluble polymer is 4.0% to 14.0%; And / or, in the internal aqueous phase, the mass concentration of the co-emulsifier is 0.5% to 5.0%; And / or, in the internal aqueous phase, the concentration of Group VIB metals as oxides is 8-80 g / 100 mL, preferably 10-60 g / 100 mL; the concentration of additives as oxides is 0-12.0 g / 100 mL, preferably 0.5-12.0 g / 100 mL. And / or, in the external aqueous phase, the concentration of Group VIII metals as oxides is 2 to 50 g / 100 mL, preferably 5 to 30 g / 100 mL; And / or, in the external aqueous phase, the mass concentration of the hydrophilic agent is 4.0% to 15.0%.
9. The preparation method according to claim 1, characterized in that, In step (3), the calcination conditions are: calcination temperature of 550-750℃, calcination time of 2-10h, and calcination atmosphere of a mixture of air and water vapor, wherein the volume ratio of air to water vapor is 0.1-5.0:1.
0.
10. The preparation method according to claim 1, characterized in that, In step (1), the preparation method of the alumina support containing the first active metal includes: (I) Mix boehmite, the first active metal, the alkaline additive, and water, grind, and filter to obtain a solid material; (II) The solid material obtained in step (I) is mixed with an adhesive, molded, dried, and calcined to obtain an alumina carrier containing the first active metal.
11. The preparation method according to claim 10, characterized in that, In step (I), the mass content of alumina in the pseudoboehmite is 60.0% to 75.0%; And / or, in step (I), the alkaline auxiliary is one or more of sodium hydroxide, potassium hydroxide, and sodium carboxylate; And / or, in step (I), the first active metal is at least one of Group VIII metals; the Group VIII metal is preferably Ni and / or Co.
12. The preparation method according to claim 10, characterized in that, In step (I), the mass ratio of pseudoboehmite (calculated as alumina): first active metal (calculated as oxide): alkaline additive: water is 200-240: 1.0-10.0: 6.0-15.0: 120-180.
13. The preparation method according to claim 10, characterized in that, In step (II), the adhesive is an organic acid and / or an inorganic acid; And / or, the inorganic acid is one or more of nitric acid, sulfuric acid, boric acid, and phosphoric acid; the organic acid is one or more of tartaric acid, citric acid, and oxalic acid; And / or, in step (II), the mass of the adhesive is 0.5% to 5.0% of the mass of boehmite in step (1) based on alumina.
14. The preparation method according to claim 10, characterized in that, In step (II), the roasting adopts a two-stage roasting process. The first stage roasting temperature is 350-450℃, the roasting time is 2-6h, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably air. The second stage roasting temperature is 450-750℃, the roasting time is 2-8h, and the roasting atmosphere is one or more of air, nitrogen, or water vapor, preferably nitrogen. Preferably, the second-stage roasting temperature is 150–300°C higher than the first-stage roasting temperature.
15. The preparation method according to claim 1, 5, 6, 7 or 8, characterized in that, In step (3), the preparation method of the "internal aqueous phase / oil phase / external aqueous phase" type impregnation solution containing the second active metal includes: (a) The surfactant and oil are mixed and heated to obtain the oil phase; (b) Mix the co-emulsifier, the Group VIB metal source, water and optional auxiliary source, and heat to obtain a clear solution; (c) Add a water-soluble polymer to the clear solution obtained in step (b) to obtain an internal aqueous phase; (d) The aqueous phase from step (c) is added dropwise to the oil phase obtained in step (a) while the oil phase remains liquid during the dropwise addition. Simultaneously, stirring and shearing are performed to homogenize the mixture, resulting in an "aqueous phase / oil phase" emulsion. (e) Mixing a Group VIII metal source with water containing a hydrophilic agent to obtain an external aqueous phase; (f) The "inner aqueous phase / oil phase" type emulsion obtained in step (d) is added dropwise to the outer aqueous phase obtained in step (e) to obtain the impregnation solution.
16. The preparation method according to claim 15, characterized in that, In step (a), the heating temperature is 45–85°C; And / or, in step (b), the heating to a temperature of 90–120°C; And / or, in step (d), the stirring-shear homogenization process is carried out at a stirring speed of 10,000 to 18,000 rpm, a homogenization time of 3 to 8 min, and a homogenization temperature of 50 to 85°C.
17. The residue hydrodemetallization catalyst prepared by any of the preparation methods described in claims 1-16.
18. The catalyst according to claim 17, characterized in that, The catalyst includes an alumina support containing a first active metal and a second active metal, wherein the first active metal is at least one of Group VIII metals and the second active metal includes at least one of Group VIB metals and at least one of Group VIII metals. Preferably, the Group VIII metal is Ni and / or Co, and the Group VIB metal is Mo and / or W.
19. The catalyst according to claim 18, characterized in that, The mass ratio of the first active metal (calculated as oxide) to aluminum oxide is 0.01 to 0.10:
1.
20. The catalyst according to claim 18, characterized in that, In the catalyst, based on the mass of the catalyst, the content of Group VIB metal oxides is 10.0% to 20.0%, and the content of Group VIII metal oxides is 2.0% to 10.0%. The mass ratio of Group VIII metal oxides in the first active metal to Group VIII metal oxides in the second active metal is 0.1 to 3.0:
1.
21. The catalyst according to claim 18, characterized in that, The catalyst includes an additive selected from at least one of phosphorus, silicon, or boron, preferably phosphorus; Preferably, in the catalyst, the content of the auxiliary agent, calculated as oxide, is 1.0% to 5.0% based on the mass of the catalyst.
22. The catalyst according to claim 18, characterized in that, The catalyst has a specific surface area of 165–185 m². 2 / g, with a pore volume of 0.60~0.85mL / g; Preferably, the catalyst has a specific surface area of 170–180 m². 2 / g, with a pore volume of 0.65~0.75mL / g.
23. The application of the catalyst according to any one of claims 17-22 in the hydrotreating of heavy oil and residual oil.
Citation Information
Patent Citations
Preparation method of hydrodemetallization catalyst
CN104549331A
